The Implementation of the Independent Learning Curriculum on Learning Achievements in Phase D of Mathematics Subjects - Adelia Maisa Fitri; Bambang Sri Anggoro; Dona Dinda Pratiwi (Bulletin of Science Education, 2024)
This research aims to analyze the implementation of the Independent Learning Curriculum in achieving learning outcomes in phase D in Mathematics subjects at SMP Negeri 21 Bandar Lampung. The Independent Learning Curriculum is a new policy that gives teachers the freedom to design relevant and contextual learning, according to students' needs and potential. The type of research used in this study is mixed methods (Mixed Method), namely combining quantitative and qualitative methods in one research. Data was collected through classroom observations, interviews with the principal, deputy principal for curriculum, and Mathematics teachers, as well as distributing questionnaires to class IX students at SMP Negeri 21 Bandar Lampung, and from student learning outcomes taken from report cards. To ensure the validity of the data, several efforts were made, namely technical triangulation and Percentages Correction. The research results show that the implementation of the Independent Learning Curriculum in phase D has a positive impact on student learning outcomes. Teachers have the freedom to choose appropriate teaching materials and learning methods, so that they can increase student involvement and motivation during the learning process. However, several obstacles were also found, such as limited resources and differences in understanding between teachers regarding the principles of the Independent Learning Curriculum. The conclusion of this research is that although there are obstacles, the implementation of the Merdeka Belajar Curriculum can improve learning outcomes in phase D in Mathematics, as long as it is supported by adequate training and resources.